Turning From Parents: Psychological Distancing and Attachment-Related Changes in Regret for Immediate Contact in Emerging Adulthood. Issue 3 (June 2020) - Dykas, Matthew J.; Siskind, Demi G.
This longitudinal study examined how emerging adults psychologically distance themselves from parents. Every week during their first semester at college, participants ( n = 71, M age = 18 years [ SD = 0.48]) read hypothetical vignettes describing emotionally salient situations they could encounter at college. Participants then provided information about whether they would regret not being in immediate contact with parents versus peers when dealing with the aftermath of these situations. Results suggested that participants were separating themselves from parents in a dynamic manner over time, which was revealed in varying levels of regret for not possibly being in immediate contact with parents following emotional events. Moreover, compared to participants with negative representational models of parents, participants with positive models reported more consistent patterns of regret for not having immediate parental contact. This study provides new insights into normative attachment dynamics beyond childhood and how emerging adults reorganize their attachment hierarchies.